The Challenges of Managing Children With Epilepsy in Africa - Wilmshurst, Jo M.; Mwesige, Angelina Kakooza; Newton, Charles R. (In Seminars in pediatric neurology, 2014)
Children with epilepsy who reside in the African continent are faced with some of the greatest challenges of receiving adequate care. The burden of disease is exacerbated by the high incidence of acquired causes and the large treatment gap. Skilled teams to identify and care for children with epilepsy are lacking. Many patients are managed through psychiatric services, thus potentially compounding the stigma associated with the condition. Little data exist to assess the true proportion of comorbidities suffered by children with epilepsy, the assumption is that this is high, further aggravated by delayed interventions and adverse responses to some of the more commonly used antiepileptic drugs.